Assessing Effects of Covid-19 Responses on Mental Health in Malawi (Poster) - Ndasauka, Yamikani; Mchenga, Martina; Kondowe, Fiskani; M'manga, Chilungamo; Kainja, Jimmy; Maliwichi, Limbika; Nyamali, Simunye (My University, 2023)
The Coronavirus Disease (Covid-19) pandemic has overwhelmed health systems in all countries, especially those in the least developing countries, Malawi included. As such, this project sought to investigate the effects of Covid-19 responses on mental health in Malawi in terms of perception toward mental health in general, the mental health of adolescents and health workers and mental health services. The project had three main phases, research, awareness campaign and dissemination.